Outcomes of Cassia Fistula Bark Hexane Extract on Serum Insulin and Glucose Levels in Diabetic Rats - Natasha Zahid, Tahira Saleem, Zainab Farooq, Faiza Anwar, Naima Khalid, Naila Ikram (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cassia fistula (amaltas) is commonly found in Pakistan and is frequently used in medicines. Its leaves, bark and pods are conventionally used for the treatment of skin disorders, bacterial infection, constipation, colic, cirrhosis, urinary disorders, dysentery, leprosy, rheumatic conditions, jaundice, syphilis, heart diseases and diabetes mellitus (DM). Aim: To determine and compare the outcomes of cassia fistula bark (hexane extract) on serum insulin and blood glucose measures in high-fat diet-fed (HFD) and Streptozotocin-induced type 2 diabetic albino male rats.” Study design: Randomized control trial. Duration and setting: Services Institute of Medical Sciences (SIMS), Lahore from August 2016 to January 2017. Methods: The research was carried out on ninety male albino rats. Rats were induced with diabetes by giving high fat diet for 2 weeks and on fourteenth day, single injection of low dose streptozotocin (25mg/kg). The rats were categorized randomly into two groups, randomly, of 45 animals each. Group 1 was diabetic control (n=45) and group 2 was diabetic experimental and was given hexane extract of Cassia fistula bark (0.45g/kg) in 1ml of 0.3 % Carboximethyl cellulose solution by using intra gastric tube for once in a day for a month. On 31st day, 4-5 ml intra cardiac blood sample was collected. Biochemical parameters serum glucose and insulin were evaluated. Results: The diabetic rats treated with hexane extract of cassia fistula bark, exhibited significant (p=0.05) decrease in serum insulin and glucose levels. Conclusion: Hexane extract of cassia fistula bark possesses potent hypoglycemic effects. Keywords: Cassia fistula, Hypoglycemic effects, diabetic rat